Nonverbal Behaviors “Speak” Relational Messages of Dominance, Trust, and Composure - Burgoon, Judee K.; Wang, Xinran; Chen, Xunyu; Pentland, Steven J.; Dunbar, Norah E. (Frontiers in Psychology, 2021)
Nonverbal signals color the meanings of interpersonal relationships. Humans rely on facial, head, postural, and vocal signals to express relational messages along continua. Three of relevance are dominance-submission, composure-nervousness and trust-distrust. Machine learning and new automated analysis tools are making possible a deeper understanding of the dynamics of relational communication. These are explored in the context of group interactions during a game entailing deception. The “messiness” of studying communication under naturalistic conditions creates many measurement and design obstacles that are discussed here. Possibilities for their mitigation are considered.